Development of a friction model for the numerical simulation of clinching processes - Max Böhnke; Christian R. Bielak; Robert Beck; Mathias Bobbert; Gerson Meschut (Friction)
In numerical simulations of mechanical joining processes, such as clinching, modeling of material behavior is of decisive importance. In addition to the correct representation of plasticity and damage mechanisms, this primarily includes modeling of the friction behavior between the parts to be joined. This paper presents a method for experimental characterization and numerical modelling of friction behavior in mechanical joining processes like clinching. An axial torsion test was used to generate surface conditions on technological specimens, which also occur in the joined parts during the clinching process. This method also enables the independent investigation of friction-relevant parameters, such as relative velocity and contact pressure. The experimental datasets using aluminum material were transferred into an analytical approach. Combined with a modifiable user subroutine, it has been implemented into the finite element (FE) modeling using LS-Dyna. Validation was performed by numerically modeling the axial torsion test and comparing experimental and numerical results. Finally, the clinching process is simulated with the developed friction model and a standard friction model, and the results are compared.